Peningkatan Kepuasan Pasien BPJS Melalui Peningkatan Empati Perawat - Arief Yanto; Edy Wuryanto; Siti Surwanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Patient satisfaction is an important element in providing better service. Patient satisfaction can be achieved by increasing nurse caring behavior. A high level of nurse empathy can be a predictor of caring attitudes possessed by nurses. This study used a quantitative associative analytic research design by using a cross-sectional approach. The study was conducted at Kendal Islamic Hospital. The samples of this study were patients of the class 3 who were BPJS participants as many as 166 respondents, which were obtained through the Proportionate Stratified Random Sampling. The results show that all respondents have the same baseline data on empathy nurses. This shows that nurses always show empathy to all patients. All variables of nursing service quality have a strong relationship with the direction of unidirectional relations, which means that the higher the quality of nursing services, the higher the value of patient satisfaction. Empathy of nurses performed when implementing nursing care in patients is the main predictor or determinant of the increase of patient satisfaction BPJS Participants at Muhammadiyah Hospital Kendal.